The Medial Offshore Record of Explosive Volcanism Along the Central to Eastern Aegean Volcanic Arc: 1. Tephrostratigraphic Correlations. (23rd December 2021) - Kutterolf, S.; Freundt, A.; Hansteen, T. H.; Dettbarn, R.; Hampel, F.; Sievers, C.; Wittig, C.; Allen, S. R.; Druitt, T. H.; McPhie, J.; Nomikou, P.; Pank, K.; et al.
Abstract: The Milos, Christiana‐Santorini‐Kolumbo (CSK) and Kos‐Yali‐Nisyros (KYN) volcanic complexes of the Aegean Volcanic Arc have repeatedly produced highly explosive eruptions from at least ∼360 ka into historic times and still show recent unrest. We present the marine tephra record from an array of 50, up to 7.4 m long, sediment cores along the arc collected in 2017 during RV Poseidon cruise POS513, which complements earlier work on distal to ultra‐distal eastern Mediterranean sediment cores. A unique set of glass‐shard trace element (LA‐ICPMS) compositions complements our major element (EMP) data on 220 primary ash layers and 40 terrestrial samples to support geochemical fingerprinting for correlations with 19 known tephras from all three volcanic complexes and with the 39 ka Campanian Ignimbrite from the Campi Flegrei, Italy. The correlations include 11 eruptions from CSK (Kameni, Kolumbo 1650, Minoan, Cape Riva, Cape Tripiti, Upper Scoriae 1 and 2, Middle Pumice, Cape Thera, Lower Pumice, Cape Therma 3). We identify a previously unknown widespread tephra from a plinian eruption on Milos (Firiplaka Tephra). Near the KYN we correlate marine tephras with the Kos Plateau Tuff, the Yali 1 and Yali 2 tephras, and the Upper and Lower Pumice on Nisyros. Between these two major tephras, we found two tephras from Nisyros not yet observed on land. The four Nisyros tephras form a systematic trend toward more evolved magma compositions. In the companion paper we use the tephrostratigraphic framework established here to constrain new eruption ages and magnitudes as a contribution to volcanic hazard assessment. Plain Language Summary: The Aegean Volcanic Arc comprises the Milos, Christiana‐Santorini‐Kolumbo and Kos‐Yali‐Nisyros volcanic complexes that present particularly high threats for humans and economy due to abundant highly explosive eruptions in the past. The systematic catalog of how eruption products are dispersed on the seafloor (marine tephras) with time provides information on the number and recurrence of eruptions, on their size, and intensities and is thus essential to quantitatively assess future volcanic hazards and risks. During RV Poseidon cruise POS513 in the Eastern Aegean Sea we recovered 50 sediment cores up to 7.4 m long. More than 220 tephra deposits (e.g., volcanic glass shards) from these eruptions were identified. Glass shard compositions from all layers were used for subsequent geochemical fingerprinting to correlate them with 19 known onshore Aegean eruptions as well as with the 39 ka Campanian Ignimbrite eruption from the Campi Flegrei, Italy. Correlations with 11 eruptions from Christiana‐Santorini‐Kolumbo are established. We identify a previously unknown widespread tephra from an eruption on Milos (Firiplaka Tephra). At the eastern region of the arc, we correlate 7 marine tephras with the Kos‐Yali‐Nisyros volcanic complex. Key Points: Marine tephrostratigraphy for the Aegean Arc Chemical fingerprinting to correlate on and offshore tephras